HUBUNGAN VERBAL ABUSE OLEH ORANGTUA DENGAN PRESTASI BELAJAR SISWA DI SMPN 2 SEDAYU BANTUL YOGYAKARTA - Lutfiyati, Afi; Eva Febri Kristiana (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
Student’s learning achievement, especially teenagers, is influenced by many factors which can often lead to the ups and downs of the student’s learning outcomes. One of those factors is family, in other words, parents. Parent’s ways of raising their children also bring a big impact on the children’s learning habit. For an example, there may be parents who care less or don’t pay any attention to their children’s learning needs at all. The effects caused by violence will keep interfering the children’s growth until they become adults and will probably result in negative behaviors in the future. The children will likely possess an aggressive behavior if the violence is done by the parents. Therefore, children’s learning can be hindered from parents’ abusive behavior. This includes verbal abuse. To identify the association between verbal abuse done by parents and students’ learning achievement. This is a cross-sectional quantitative study. The sample were chosen through stratified random sampling, which included 119 students of SMPN 2 Sedayu Bantul Yogyakarta. The research used questionnaire verbal abuse and the students’ final semester test scores as the instruments.The data were analyzed using kendall’s tau test. Vebal abuse by parent majority in moderate category as much 84 student (70,6%). For student achievement majority in moderate category as much 104 student (87,4%). From kendall’s tau test it was found that p-value=0,074 (>0,05), meaning that there were no association between verbal abuse done by parents and students’ leaning achievement. There were no association between verbal abuse done by parents and student’s of SMPN 2 Sedayu Bantul Yogyakarta learning achievement.